Nonlinear analysis of a building surmounted by a reinforced concrete water tank under hydrostatic load. (March 2018) - Ait L'Hadj, Lamia; Hammoum, Hocine; Bouzelha, Karima
Highlights: An approach for assessing the damage level of an existing structure under seismic action is proposed. The nonlinear analysis is performed by structural finite element software to obtain the capacity curve. The performance point is positioned in European macroseismic scale to deduce the damage level of the structure. As a case study, an apartment building surmounted by a RC water tank is analysed. This proposed method fits into a practical environment of the engineering by combining analysis software with design codes. Abstract: This work presents a methodology for assessing the damage level of an existing structure under seismic action. First, the seismic demand is introduced by the response spectrum provided by the seismic code, and then the nonlinear static equivalent analysis is performed by structural finite element software to obtain the capacity curve. The evaluated performance point according to the pushover analysis is positioned in European macroseismic scale in order to deduce the damage domain of the structure. The effectiveness of this proposed method is tested successfully for a real case. As a practical application, we analyse a highly complex structure which is an apartment building in Algiers surmounted by a reinforced concrete water tank with a container capacity of 1000 m 3 . It is complex in its design and analysis, and complex also by its behaviour under earthquake effect. Since being commissioned in 1962, this structure has been subjected to several earthquakes, but the one that hit Boumerdes town on 2003, was fatal for it. The proposed approach classifies the studied structure in the third domain; which describes a very important state of damage. This work fits into a practical environment of the engineering by combining analysis software with design codes and by the applicative character of the proposed approach.